2017
DOI: 10.1159/000473694
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Age Cutoff Criterion for Reporting Benign-Appearing Endometrial Cells in Routine Pap Tests: An 8-Year Retrospective Review

Abstract: Objective: The 2014 Bethesda System recommends that benign-appearing endometrial cells (BECs) in routine Pap tests should be reported in patients aged ≥45 years. This is a change from previous guidelines to report BECs in women ≥40 years of age. BECs are reported to have 1% chance of endometrial lesion on follow-up. This study tests whether the new threshold may increase the specificity of the test for the detection of clinically significant endometrial lesions. Study Design: After institutional review board a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Some studies have argued that the evaluation of the endometrial cells in the Pap test according to the menopausal state or the presence of symptoms is more valuable in detecting pathologies (8,9). Thereupon, studies have been proposed involving different age limits and various variables (8,(10)(11)(12)(13)(14)(15). In our study, no pathological lesions were found in women between the ages of 40-45 and 46-49, in contrast to women aged 50 and over, most of whom were postmenopausal and had pre-neoplastic and neoplastic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have argued that the evaluation of the endometrial cells in the Pap test according to the menopausal state or the presence of symptoms is more valuable in detecting pathologies (8,9). Thereupon, studies have been proposed involving different age limits and various variables (8,(10)(11)(12)(13)(14)(15). In our study, no pathological lesions were found in women between the ages of 40-45 and 46-49, in contrast to women aged 50 and over, most of whom were postmenopausal and had pre-neoplastic and neoplastic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…References were reviewed and no evidence was found to change the 2012 recommendations. [85][86][87][88][89][90][91][92][93]…”
Section: G4 Benign Endometrial Cells In Premenopausal Patients or Bementioning
confidence: 99%